2014
DOI: 10.1186/1471-2393-14-127
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the prevalence of prenatal alcohol exposure obtained via maternal self-reports versus meconium testing: a systematic literature review and meta-analysis

Abstract: BackgroundMaternal self-reports, used for the detection of prenatal alcohol exposure (PAE), may lack validity, necessitating the use of an objective biomarker. The detection of fatty acid ethyl esters (products of non-oxidative ethanol metabolism) in meconium has been established as a novel biomarker of PAE. The purpose of the current study was to compare the prevalence of PAE as reported via maternal self-reports with the results of meconium testing, and to quantify the disparity between these two methods.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(99 citation statements)
references
References 46 publications
1
97
0
1
Order By: Relevance
“…In relation to EtG, different cut-offs have been proposed (30 and 50 ng/mg) to disclosing intrauterine exposure to ethanol but EtG lacks a universally established cut-off value at the present time [10][11][12]. However, the degree of agreement between detection of ethanol metabolites in neonatal meconium and maternal self-reported ethanol intake during pregnancy remains unclear [4][5][6][7][8][9][13][14][15][16][17][18][19]. It has been shown that reliance on maternal self-reporting is associated with a high probability of error, with substantial underreporting [14,18,20,21].…”
Section: Introductionmentioning
confidence: 98%
“…In relation to EtG, different cut-offs have been proposed (30 and 50 ng/mg) to disclosing intrauterine exposure to ethanol but EtG lacks a universally established cut-off value at the present time [10][11][12]. However, the degree of agreement between detection of ethanol metabolites in neonatal meconium and maternal self-reported ethanol intake during pregnancy remains unclear [4][5][6][7][8][9][13][14][15][16][17][18][19]. It has been shown that reliance on maternal self-reporting is associated with a high probability of error, with substantial underreporting [14,18,20,21].…”
Section: Introductionmentioning
confidence: 98%
“…This raises the possibility that pregnant women who report drinking modest amounts of alcohol could be detected by the self-report reference standard but not the index test. 103 This explanation is not likely to account for findings in the present review, however, because the majority of studies investigated moderate to heavy self-reported PAE. CI, confi dence interval; LC/MS/MS liquid chromatography tandem mass spectrometry; LR+, positive likelihood ratio; LR-, negative likelihood ratio; NPV, negative predictive value; PPV, positive predictive value; sens, sensitivity; spec, specifi city.…”
Section: Limitations Of the Evidencementioning
confidence: 65%
“…Furthermore, in Ontario (Canada) the close follow-up of a baby identified as 'at risk' for alcohol-related disabilities facilitated early detection of developmental delays and initiation of interventions [7]. In a study comparing the prevalence of prenatal alcohol exposure obtained via maternal self-reports versus meconium testing, the pooled prevalence of alcohol exposure by meconium testing was 4.26 (95% Confidence Interval 1.34-13.57) times the pooled prevalence as measured by maternal self-reports [1]. A decision analytic model was developed to assess the cost-effectiveness of analyzing meconium.…”
Section: Fatty Acid Ethyl Esters (Faee)mentioning
confidence: 99%
“…In order to diagnose a child with FAS or FASD, maternal alcohol consumption during pregnancy needs to be proven. This makes the diagnosis of FAS and FASD a difficult one since self-reported questionnaires underreport the use of alcohol and are therefore biased [1]. Further, research regarding the harmful effects of alcohol during pregnancy is mostly performed with such questionnaires, so results of this kind of research is doubtful.…”
mentioning
confidence: 99%